Combined radiotherapy and hysterectomy in the treatment of high risk stage II invasive carcinoma of the uterine cervix. - S. Srisupundit (2018)
This is a prospective non-randomized study of 127 patients with stage IIB carcinoma of the cervix treated with irradiation and followed by surgery at Ramathibodi Hospital between 1980 and 1989. The criteria for combined treatment were an enlarged cervical mass of over 5 cm, including a barrel-shaped cervix, inadequate or improper radium insertion due to obliterated cervical os, and endometrial extension. The 5-year survival rate was 84.37%. The incidence of pelvic failure was 10.2% and extrapelvic failure was 6.3%. Those revealing residual disease in hysterectomy specimens had a worse prognosis. The increase in the survival rate in this study as compared to other reports may have been due to the use of higher dosages of irradiation. It is concluded that combined treatment was effective in dealing with poor prognosis groups of carcinoma of the cervix. It improved the pelvic and extrapelvic control as well as the survival rate with acceptable complications.